2021
DOI: 10.21203/rs.3.rs-494322/v1
|View full text |Cite|
Preprint
|
Sign up to set email alerts
|

WITHDRAWN: Repurposing of Dapsone as Neuroprotective Agent on Cuprizone-induced Demyelination via Targeting Nrf2 and NF-kB in C57BL/6 Mice

Abstract: Multiple Sclerosis (MS) is an inflammatory disorder wherein the myelin of nerve cells in central nervous system is damaged. Fatigue, lack of coordination, blurred vision and mental problems are some of the symptoms of MS. In the current study, we assessed the performance of Dapsone (DAP) on improvement of behavioral dysfunction and preservation of myelin in the cuprizone (CPZ) induced demyelination model via targeting Nrf2 and IKB. MS was induced in C57BL/6 mice through diet supplementation of CPZ (0.2%) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Accumulating evidence has confirmed that single-dose administration of dapsone inhibits the inflammatory pathways in different animal models such as testicular torsion/detorsion, acetic-acid induced inflammatory bowel disease, and cuprizone-induced demyelination. 8,36,37 Notably, there is evidence that dapsone improved the anti-convulsant activity of diazepam in the kainic acid-induced SE in rats; 38 however, the anti-epileptic effect of dapsone on pro-inflammatory cytokines including TNF-α and the NO signaling pathway in the lithium pilocarpine-induced SE is still unknown. We observed that dapsone could effectively alleviate the enhanced level of NO and TNF-α during SE development.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has confirmed that single-dose administration of dapsone inhibits the inflammatory pathways in different animal models such as testicular torsion/detorsion, acetic-acid induced inflammatory bowel disease, and cuprizone-induced demyelination. 8,36,37 Notably, there is evidence that dapsone improved the anti-convulsant activity of diazepam in the kainic acid-induced SE in rats; 38 however, the anti-epileptic effect of dapsone on pro-inflammatory cytokines including TNF-α and the NO signaling pathway in the lithium pilocarpine-induced SE is still unknown. We observed that dapsone could effectively alleviate the enhanced level of NO and TNF-α during SE development.…”
Section: Discussionmentioning
confidence: 99%